1095. Investigation of Risk Factors Associated with Serious Bacterial, Viral and Invasive Fungal Infections in Hematologic Patients on Ibrutinib. (31st December 2020) - Holowka, Thomas; Cheung, Harry; Malinis, Maricar F; Perreault, Sarah; Isufi, Iris; Azar, Marwan M
Abstract: Background: Ibrutinib is a tyrosine kinase inhibitor used to treat hematologic malignancies that may increase the risk of serious infection including invasive fungal infections (IFI). In a study of 378 patients with hematologic malignancy on ibrutinib, serious infection and IFI occurred in 11% and 4% respectively (Varughese et al. Clin Infect Dis ). The primary aims of our study were to determine the incidence of serious infection and associated risk factors in patients on ibrutinib. Methods: We performed a retrospective analysis of patients with hematologic malignancy prescribed ibrutinib for ≥ 1 week at Yale New Haven Hospital from 2014 to 2019 to identify serious infections defined as those requiring inpatient management. We collected demographic, clinical and oncologic data. Chi-squared tests were used to determine factors associated with an increased risk of infection. Results: A total of 254 patients received ibrutinib including 156 with CLL, 89 with NHL and 9 with other leukemias. Among these, 21 underwent HSCT, 9 complicated by GVHD. There were 51 (20%) patients with serious infections including 45 (17.7%) bacterial, 9 (3.5%) viral and 5 (2%) IFI (1 pulmonary cryptococcosis, 4 pulmonary aspergillosis). Anti-mold prophylaxis was prescribed to 7 (2.8%) patients, none of whom developed IFI. Risk factors associated with serious infection included ECOG score ≥ 2 (OR 4.6, p < 0.001), concurrent steroid use (≥ 10 mg prednisone daily for ≥ 2 weeks; OR 3.0, p < 0.001), neutropenia (OR 3.6, p < 0.01), lymphopenia (OR 2.4, p < 0.05) and maximum ibrutinib dose of 560 mg (OR 2, p < 0.05). There was a dose dependent increase in infections based on number of chemotherapy regimens prior to ibrutinib initiation: 14.3% with 0, 19.7% with 1-2 and 28.7% with ≥ 3 prior treatments. Conclusion: The incidence of serious infection in hematologic patients on ibrutinib was higher than previously reported (20% versus 11%) but the rate of IFI was lower (2% versus 4%). High ECOG score, leukopenia, steroids, and higher ibrutinib doses were associated with an increased risk for serious infection. Targeted antimicrobial prophylaxis should be considered for patients on ibrutinib with these risk factors. Improving functional status may also reduce the risk of infection in patients on ibrutinib. Disclosures: All Authors : No reported disclosures